Features of Clinical Course of Perforated Ulcers of Stomach and Duodenum in Children - A.G. Zaporozhchenko; A.P. Gladky; O.V. Dovbysh; O.V. Spakhi (Zdorovʹe Rebenka, 2013)
We examined 52 patients aged from 14 to 17 years with perforated ulcer of stomach and the duodenum, operated using laparoscopic and open ways. It is established, that perforated ulcer of stomach and the duodenum in children onset suddenly, the are characterized by absence of «ulcer anamnesis» and clinical picture of acute peritonitis in 77 % of children. Maximum efficiency of diagnosis of perforated gastric and duodenal ulcers is achieved by using a comprehensive diagnostic program that includes the use of phased diagnostic measures in accordance with their resolution in each case.